2016
DOI: 10.1182/blood.v128.22.1087.1087
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Genetic and Clinical Analysis through Whole Exome Sequencing in 1001 Diffuse Large B Cell Lymphoma (DLBCL) Patients Reveals Novel Disease Drivers and Risk Groups

Abstract: Introduction Diffuse large B cell lymphoma (DLBCL), the most common lymphoma world-wide, is strikingly heterogeneous. This heterogeneity creates a daunting challenge for conducting well-powered studies connecting molecular features to clinical outcome. Not only is the association of genetic mutations with clinical outcome in DLBCL mostly unknown, the relative importance of other well-described features, such as MYC and BCL2 translocation/expression and cell of origin based subsets (ABC and GCB D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…1). Transcriptomic and genomic analyses identified recurrent genomic aberrations and signaling pathway alterations unique to each subtype and common to both (2,3). Mutations in genes altering B-cell receptor (BCR) signaling and NFkB activation (e.g., CD79A, MALT1, and MYD88) are more common in ABC DLBCL, whereas mutations in genes altering histone modifications and B-cell homing (e.g., EZH2, CREBBP, and MLL2) are more common in GCB DLBC (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1). Transcriptomic and genomic analyses identified recurrent genomic aberrations and signaling pathway alterations unique to each subtype and common to both (2,3). Mutations in genes altering B-cell receptor (BCR) signaling and NFkB activation (e.g., CD79A, MALT1, and MYD88) are more common in ABC DLBCL, whereas mutations in genes altering histone modifications and B-cell homing (e.g., EZH2, CREBBP, and MLL2) are more common in GCB DLBC (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…Mutations in TP53, immunosurveillance genes (e.g., B2M, CD58), epigenetic modifiers (e.g., CREBBP), and MYC copy number alteration (CNA) gains occur in both subtypes (2). Whole-genome and -exome sequencing efforts have identified over 300 recurrently mutated genes in primary DLBCL samples (3,5,7,8). However, there is still limited knowledge on functional impact of many of these mutations and genetic alterations on disease initiation and progression; genetically engineered mouse models (GEMM) provide a platform to begin evaluating these putative targets.…”
Section: Introductionmentioning
confidence: 99%
“…Another study found that concurrent MYC, BCL2 and/or BCL6 chromosomal translocations (in so-called double- or triple-hit lymphomas) were also predictive of clinical outcomes when combined with the cell-of-origin classification [35]. A recent study combining whole-exome and transcriptome analysis as well as single nucleotide polymorphism (SNP) arrays in >1000 DLBCL patients [36] has identified other mutations associated with poor survival that could be targeted with new therapies.…”
Section: Discussionmentioning
confidence: 99%
“…New genomic data presented at ASH 2016 emphasize the power of having large numbers of cases to better contextualize putative drivers. Zhang et al (2016) carried out what could possibly be the largest whole-exome sequencing study of any individual cancer type, by analyzing the genomes of 1001 de novo DLBCL patients. Forty-two novel drivers were identified, including the aforementioned BTK .…”
Section: Drivers Versus Passengers: the Aid Effectmentioning
confidence: 99%